Visible light driven photocatalytic activity of unsubstituted and Ag1+ / Al3+-substituted CuO nanoflakes. Issue 9 (15th June 2020) - Khalid, Muhammad Usman; Warsi, Muhammad Farooq; Sarwar, Muhammad Ilyas; Agboola, Philips O.; Shakir, Imran; Zulfiqar, Sonia
Abstract: Unsubstituted and (Ag 1+ & Cu 2+ ) substituted CuO nanoflakes were prepared using simple co-precipitation technique. Structural and morphological investigations were performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM) respectively. XRD analysis confirmed the monoclinic crystal structure of all compositions of CuO nanoflakes. SEM analysis confirmed the-flake like morphology of CuO. Energy dispersive X-ray spectroscopy (EDX) confirmed the decreased oxygen contents in various derivatives of CuO flakes. This indicated the substitution of Cu 2+ ions with Ag 1+ and Al 3+ ions. UV–visible analysis showed that all derivatives of CuO nanoflakes absorbed light in the entire visible region, thus proved potential candidate to harvest solar radiations. Optical bandgap value was found to show red shift with Ag 1+ substitution and blue shift with Al 3+ substitution. Ag proved itself a potential candidate towards the electrical conductivity improvement. The photocatalytic activity was found to increase with modified CuO nanoflakes. The maximum photocatalytic efficiency was observed by Ag-doped CuO nanoflakes.